Bismuth Detection in Alkaline Electrolyte via Anodic Stripping Voltammetry for Battery Separator Evaluation. Issue 3 (23rd November 2020) - Arnot, David J.; Lambert, Timothy N.
Abstract: Anodic stripping voltammetry (ASV) has been widely used for the detection of several heavy metal ions in neutral and acidic solution, in many cases employing electrodes and/or solutions incorporating Bi. In this work we demonstrate that Bi(OH)4 − ion concentration can be measured in highly alkaline 8.5 M KOH solution using ASV. The addition of Pb in similar concentrations to the Bi(OH)4 − being measured is shown to improve both the sensitivity and precision of the method. When the Pb additive is employed, a formal limit of detection of 8.5 ppb is achieved, compared to 17.3 ppb when the Pb additive is not used. Due to the use of Bi additives in alkaline battery chemistries, it follows that separators which limit Bi(OH)4 − diffusion into the bulk electrolyte and away from the electrodes are of interest. For this purpose, we utilize ASV to determine Bi(OH)4 − diffusion rates through Celgard 3501, cellophane 350P00, and Nafion 211. Bi(OH)4 − crossover rates, as determined by ASV, are shown to be repeatable and consistent with expectations from the known separator structure. Abstract :